Apollo in the North: Transmutations of the Sun God in Walter Pater’s Imaginary Portraits - Lene Østermark-Johansen (Cahiers Victoriens et Edouardiens)
Walter Pater’s fascination with the Hyperborean Apollo, who according to myth resided north of the home of the northern wind, is explored in two of his pieces of short fiction, ‘Duke Carl of Rosenmold’ (1887) and ‘Apollo in Picardy’ (1893). The essay discusses some of Pater’s complex dialogue with Victorian science, mythography and folklore in the texts, in an attempt to map the topicality of his fiction. Although he chose historical settings in medieval France and eighteenth-century Germany for his tales, they reflect recent debates about the disappearance of the sun and the folkloristic animalism of Apollo the nature god. Furthermore, Pater is engaging in a complex geopolitical argument, playing out German, French and English culture against each other, as he traces the survival of the pagan gods after the onset of Christianity. The myth of the Hyperborean Apollo is a myth about the North: where does it begin? Where does it end? Is it a place of light or of darkness? Pater’s dark Apollo challenges conventional notions of the sun god and testifies to the strong presence of paganism in Pater’s late writings.